KAJIAN KUALITAS SEMEN AYAM MIRAH DARI DUA GENERASI YANG BERBEDA (Study of The Quality of Mirah Chicken Semen from Two Different Generation) - Silalahi, Parsaoran; Tafanao, Imel; Silalahi, Zuaber; Manalu, Sandi (Universitas Nusa Cendana, 2025)
Mirah Chicken is a native chicken that has long been developed in Simalungun Regency and is thought to originate from the red jungle fowl (Gallus gallus). Currently, Mirah Chicken is used as a culinary ingredient known as Dayok Nabinatur. The population Mirah Chicken is yet known, but extensive Mirah Chicken breeders are still found in Simalungun Regency. To increase the population and make reproduction more efficient, mating with artificial insemination is applied to the Mirah Chicken population developed at the Faculty of Animal Husbandry, UHN. Therefore, the purpose of this study was to examine the quality of Mirah Chicken semen that will be used in the artificial insemination process. The basic population of Mirah Chickens was obtained from breeders in Simalungun Regency, where this basic population (G-D) has produced the first generation (G-1), which has reached a productive age of 8 months. The number of G-D and G-1 chickens used in this study was 5, respectively. The semen collection method was carried out by the massage method. The collected semen was evaluated macroscopically and microscopically in the livestock reproduction laboratory. The results of macroscopic evaluation showed that the volume of semen ranged from 0,14-0,18 ml/ejaculate, with a normal pH of 7,52-7,62, then the color of the semen was milky white, and the consistency was thick. The results of microscopic evaluation showed that the mass movement ranged from 1,4-2,0, and progress motility was around 72-74%. The sperm concentration parameter showed 8,12-10,47 x109 spermatozoa cells/ml with an abnormality of around 18,2-19,0%. The results of statistical analysis showed that there was no difference between G-D and G-1 for all parameters and it can be concluded that the quality of Mirah Chicken semen is classified as normal and can be used for artificial insemination.